The Existence of Subgame-Perfect Equilibrium in Continuous Games with Almost Perfect Information: A Case for Public Randomization - Harris, Christopher; Reny, Philip; Robson, Arthur (Econometrica, 1995)
Christopher Harris, Philip Reny, Arthur Robson, The Existence of Subgame-Perfect Equilibrium in Continuous Games with Almost Perfect Information: A Case for Public Randomization, Econometrica, Vol. 63, No. 3 (May, 1995), pp. 507-544